Assessment of physical, chemical and dissolved trace metals parameters of marine water quality in East Malaysia’s port / Wan Nur Fazlina Abdol Jani … [et al.] - Abdol Jani, Wan Nur Fazlina; Suja’, Fatihah; Mohamad Hamzah, Firdaus; Md Zain, Shahrom (Universiti Teknologi MARA, 2021)
A port is an important national asset that needs to be carefully protected. Ports should be maintained to preserve both public health and the natural environment. This study focused on determining the status of a port in Peninsular Malaysia based on water quality analysis. Marine water samples in the port were collected from eight sampling locations. Fifteen physical and chemical parameters and trace metal concentrations were measured in-situ and in a laboratory using standard methods. The ranges of the results were as follows; 26.6–32.2 °C for temperature, 7.2–9.5 for pH, 7.18–8.55 mg/L for DO, 6.27–423.33 NTU for turbidity, 41–751 mg/L for TSS, 1.1–10.5 mg/L for BOD5, 57–2791 mg/L for COD, 6.00–679.50 mg/L for O&G, and 0.17–7.28 mg/L for NH3–N. The trace metal concentrations were as follows; 0.000–0.080 mg/L for Al, 0.000–0.048 mg/L for Cr, 0.001–0.197 mg/L for Cu, 0.002–0.821 mg/L for Fe, 0–0.038 mg/L for Ni, and 0.001– 0.068 mg/L for Zn. The parameters of total suspended solid, chemical oxygen demand, oil and grease, ammonia-nitrogen and Cu were mostly unacceptable in terms of water quality and sources of pollution. It stemmed from the phenomenon of the tides, port activities and the diversity of shipload, effects of antifouling ship, sewage and storm water runoff are the main contributors of marine pollution. Therefore, water quality monitoring and control of the release of untreated organic and dissolved metal wastes into marine waters are greatly needed.